PENGARUH NILAI YANG DITERIMA PELANGGAN DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN : KEPUASAN PELANGGAN SEBAGAI MEDIATOR DAN GENDER SEBAGAI MODERATOR - Evan Chandra Kusuma (University of Merdeka Malang, 2018)
The objective of this study is to examine and analyze the direct impact of perceived value and service quality on customer satisfaction and customer loyalty. This study also examine and analyze the indirect impact of perceived value and service quality on customer loyalty with customer satisfaction as mediation variable. In addition, it also examine the indirect impact of perceived value, service quality, and customer satisfaction on customer loyalty with gender as moderation variable.The study surveyed a sample of 120 respondents in Kota Baru Train Station in Malang City. Purposive sampling was chosen as a method to determine the samples. The study used Partial Least Square (PLS) - Structural Equation Model (SEM) as analytical tools to test the hypothesis. The results showed that perceived value and service quality has impact on customer satisfaction, perceived value and customer satisfaction has an impact on customer loyalty, service quality has no significant impact on customer loyalty, customer satisfaction mediates the impact of perceived value on customer loyalty, customer satisfaction mediates the impact of service quality on customer loyalty, gender has not moderatory impact of perceived value, service quality,and customer satisfaction on customer loyalty. DOI : https://doi.org/10.26905/jbm.v5i1.2315